The Correlation between Vocational Students’ Speaking Anxiety and Speaking Performances in Learning English - Shiken Anzanni; Dian Novita Dewi (Institut Agama Islam Negeri Palopo, 2022)
Speaking is one of English skills that needs to be mastered by the students because it is the most fundamental element to build a communication. However, speaking has the complexity that can difficult the students to learn English and reach the goal. This study aims to find out about the correlation between vocational students’ speaking anxiety and speaking performances in learning English. This study also find out about their speaking anxiety level, type of speaking anxiety, and their speaking ability in learning English. A correlational study used to conduct this research. The researcher collected the data through FLCAS questionnaire that consists of 24 statements and the students’ speaking performance score. The researcher distributed the questionnaire to 70 students of SMK PGRI 3 Malang. After analyzing the findings with SPSS version 24 and Microsoft Excel, the result shows that there is a negative correlation between students’ speaking anxiety and speaking performances in learning English. It is correlated at -0.192 which means it is in a very weak correlation. In addition, the students’ speaking anxiety level is identified in moderate level. The dominant type of speaking anxiety they have is communication apprehension and their speaking ability is categorized in a very good level.